2018
DOI: 10.1101/gr.234872.118
|View full text |Cite
|
Sign up to set email alerts
|

Young genes have distinct gene structure, epigenetic profiles, and transcriptional regulation

Abstract: Species-specific, new, or "orphan" genes account for 10%-30% of eukaryotic genomes. Although initially considered to have limited function, an increasing number of orphan genes have been shown to provide important phenotypic innovation. How new genes acquire regulatory sequences for proper temporal and spatial expression is unknown. Orphan gene regulation may rely in part on origination in open chromatin adjacent to preexisting promoters, although this has not yet been assessed by genome-wide analysis of chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 98 publications
(121 reference statements)
7
68
2
Order By: Relevance
“…Our study provides empirical support for the hypothesis that enhancers may facilitate de novo gene evolution, which to our knowledge was first proposed upon the discovery of enhancer RNA (Kim, et al 2010) and later expanded upon in a perspective piece by Wu and Sharp (Wu and Sharp 2013). Our findings complement recent work on the regulatory architecture of the nematode Pristionchus pacificus, which showed that young genes – those private to P. pacificus – are in closer proximity to enhancers than genes with one-to-one orthologs in other nematode species (Werner, et al 2018). The observation that many young ORFs are proximal to enhancers in both nematodes and mammals suggests that this mode of gene evolution dates back to at least the common ancestor of Bilateria, and possibly even earlier, since cnidarians, ctenophores, and sponges also employ distal regulatory elements (Schwaiger, et al 2014; Gaiti, et al 2017; Sebé-Pedrós, et al 2018; Sebé-Pedrós, et al 2018).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our study provides empirical support for the hypothesis that enhancers may facilitate de novo gene evolution, which to our knowledge was first proposed upon the discovery of enhancer RNA (Kim, et al 2010) and later expanded upon in a perspective piece by Wu and Sharp (Wu and Sharp 2013). Our findings complement recent work on the regulatory architecture of the nematode Pristionchus pacificus, which showed that young genes – those private to P. pacificus – are in closer proximity to enhancers than genes with one-to-one orthologs in other nematode species (Werner, et al 2018). The observation that many young ORFs are proximal to enhancers in both nematodes and mammals suggests that this mode of gene evolution dates back to at least the common ancestor of Bilateria, and possibly even earlier, since cnidarians, ctenophores, and sponges also employ distal regulatory elements (Schwaiger, et al 2014; Gaiti, et al 2017; Sebé-Pedrós, et al 2018; Sebé-Pedrós, et al 2018).…”
Section: Discussionsupporting
confidence: 89%
“…S1 shows that these trends are not driven by exon length). Taken together, these results support a model in which enhancers facilitate the expression of young ORFs (Wu and Sharp 2013; Werner, et al 2018).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…This shows that the chromatin states of promoters of simple duplicated genes can evolve independently in each pair. This could correspond to the differential chromatin states recently identified in new genes in nematodes (Werner et al 2018), since in each pair, one gene is more recent than the other.…”
Section: Chromatin Accessibility Is Altered In Young Duplicated Genesmentioning
confidence: 71%
“…The species shared their last common ancestor around 100 million years ago, which is longer than the human-mouse separation (nei and Glazko, 2001;Prabh et al, 2018;Rota-Stabelli et al, 2013;Werner et al, 2018), and have since diverged to populate very discrete habitats and engage in distinct sets of behaviors. C. elegans is a free-living nematode that can mainly be found in rotten fruit while members of the genus Pristionchus are regularly found in association with several species of scarab beetles {Herrmann 2006b; Herrmann 2007, (Koneru et al, 2016;Ragsdale, 2015).…”
Section: Introductionmentioning
confidence: 99%